Perinatal outcomes of fetal echogenic bowel. (7th June 2011) - Saha, E; Paramasivam, G; Mullins, E; Kumar, S; Lakasing, L
Abstract : Objective: To investigate perinatal outcomes of fetal echogenic bowel (FEB). Methods: This is a retrospective observational study of FEB cases referred between January 2005 and December 2010. Data was obtained from Fetal Medicine, Obstetric, Neonatal Databases. Results: There were 139 cases, mean gestation 21 +5 (15 +1 –35 +5 ) weeks. 53 (38%) had fetal karyotyping. Of the six abnormal results, all had other structural anomalies. 66 (47%) were screened for toxoplasma and cytomegalovirus. The two cases of confirmed fetal cytomegalovirus infection both had additional ultrasound markers. One had termination of pregnancy (TOP), the other developed fetal hydrops at 33 weeks. 44 couples were screened for cystic fibrosis, 2 had carrier status but partners screened negative. Uterine Artery Doppler (UAD) screening was performed in 120 women. Of the 99 (82.5%) who screened negative (Mean PI <1.45), there were no cases of pre-eclampsia, 3 had fetal growth restriction (FGR) at term (birth weight <5th centile). Of the 21 (17.5%) who screened positive (mean PI ≤1.45), six had intrauterine deaths (25–31 weeks) from placental abruption ± FGR, one TOP for severe FGR (23 weeks), two lost to follow-up and four live births >36 weeks. Overall, there were 106 live births, 16 (15%) preterm, 26 (24.5%) required special care for 15 (1–78) days, 102 established enteral feeds, none had primary bowel pathology. Conclusion: FEB associated with chromosomal abnormality and congenital infection had other ultrasound anomalies. Isolated FEB was associated with a high incidence of placental insufficiency, FGR and poor perinatal outcome, especially in cases with abnormal UAD.